An experimental study on the effect of grammatical structure on cheating behavior - Chen, Jiajing (2016)
Pronoun drop and its correlation to cheating behavior has been a popular topic amongst researchers these days. However, analysis done by past studies were based on observational data and were unable to draw causal conclusion between pronoun “I” and individuals’ cheating tendencies. Hence, this paper serves as the first experimental study to examine the causal relationship between pronoun “I” and cheating. It also aims to investigate how pronoun use would affect the ‘Self’; which propels one to cheat. 82 undergraduates from Nanyang Technological University took part in the study, which is programmed using Ztree. The experiment was structured with a between-subject design to control for pronoun use and included a primary coin-tossing task to detect cheating on the group level. In addition, secondary tasks were included to measure how pronoun “I” influences Self-Interest, Private Self-Consciousness and Self-Inflation. The findings show that use of first person singular pronoun leads to increased cheating tendencies. It further established that the ‘Self’ serves as a probable reason for cheating when pronoun “I” is utilised. In particular, the use of pronoun “I” would elevate subjects’ levels of Self-Interest and decrease levels of Private Self-Consciousness. Overall, the findings serve as a point of consideration for policy-makers when garnering responses, whether using pronoun “I” would elicit truthful replies or would individuals be self-interested and more prone to cheat. Key Words: Experimental; Pronoun; Self; Cheating